Indigenous peoples need to coexist without being stripped of their culture (Journal of Parents and Teachers, 2026)
Following the awarding of the Nobel Peace Prize to Guatemalan Rigoberta Menchú, the media frequently covers the situation of the indigenous population in America. Here are some facts on the subject that can be used in social studies classes. Meanwhile, on the initiative of the Ministry of Health and Humanitarian Action, French children have carried out the ‘kilo by kilo’ campaign, delivering 6,000 tonnes of rice so that Somali children could eat for a month. You will find these and other ideas in this section. In addition, you will find a reading method for the first year of life and the story of the production of a very special tomato.
Keywords: indigenous peoples, culture, solidarity campaign, early reading, special tomato